Ambang Batas Pencalonan Presiden Dan Wakil Presiden Terhadap Perlindungan Hak Konstitusional Warga Negara : Analisis Putusan Mahkamah Konstitusi Nomor : 53/PUU-XV/2017 - Hendra Poltak Tafonao; Faisal Akbar Nasution; Mirza Nasution; Afnila Afnila (Universitas Sumatera Utara, 2019)
Abstract. The imposition of a threshold on constitutional presidential elections violates the constitutional rights of citizens. Based on the provisions of Chapter 6A Verse (2) of the 1945 Constitution, the presidential candidate and vice presidential candidate pairs are proposed by political parties or a combination of political parties participating in the general election before the general election. This provision provides space for political parties to propose candidates for president and vice president. but in article 222 of law number 7 of 2017 concerning general elections it provides a limit of 20% of the number of seats in the DPR or 25% of nationally valid votes in previous DPR member elections. in a presidential system the imposition of a threshold is irrelevant because theoretically separation of power is not known as the existence of a presidential accountability to the parliament, thus the threshold is not appropriate if the votes used are from the DPR elections. for this reason, the decision of the constitutional court should provide justice for the people by considering the sovereignty of the people. Keywords: threshold, presidential election, constitutional court decision.